Hyaluronic acid functionalized copper-cerium bimetal peroxide nano octahedron with controllable size as well as preparation method and application of hyaluronic acid functionalized copper-cerium bimetal peroxide nano octahedron
Through the preparation of hyaluronic acid-functionalized copper-cerium bimetal peroxide nano-octahedral, the shortcomings of existing copper-cerium bimetallic nanodrugs in particle structure and catalytic effects are solved, and high efficiency in the tumor microenvironment is achieved Oxidative stress and immune response have significantly improved the efficacy of tumor treatment.
Patent Information
- Application Number
- CN202411341007.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-09-25
AI Technical Summary
The existing copper-cerium bimetallic nanodrugs have shortcomings in particle structure and catalytic effects, which are difficult to meet different usage needs, and the symmetry of the spherical structure and limited catalytic activity limit their effectiveness in tumor treatment.
The preparation method of hyaluronic acid-functionalized copper-cerium bimetallic peroxide nano-octahedral is adopted. By adjusting the molecular weight of polyvinylpyrrolidone and the feed concentration of sodium hydroxide, the size and morphology of nanoparticles are controlled to form an octahedral structure. Improve its reactive oxygen generation ability and targeting ability in the tumor microenvironment.
Nanopharmaceuticals with controllable size, high stability, and strong bimetallic synergistic catalysis ability can effectively produce toxic ROS in the tumor microenvironment, enhance oxidative stress of tumor cells, promote immune response, and significantly improve the tumor treatment effect.
Smart Images

Figure CN119235915A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of biomedicine technology, and in particular to a size-controllable hyaluronic acid functionalized copper-cerium bimetallic peroxide nano-octahedron, and a preparation method and application thereof. Background Art
[0002] The mortality rate caused by malignant tumors has increased year by year and has become a key public health issue affecting human life and health. At present, the clinical treatment method for tumors is still the traditional treatment method based on radiotherapy and chemotherapy. However, due to the existence of the tumor microenvironment, the complexity and heterogeneity of tumors limit the further development and application of traditional radiotherapy and chemotherapy techniques. For example, tumor cells metabolize glucose in a glycolytic manner, causing the pH value of the tumor microenvironment to be maintained between 6.5 and 6.8, activating drug resistance mediated by multiple signaling pathways. At the same time, non-specific radiotherapy and chemotherapy techniques can cause strong toxic side effects on normal tissues and organs. Therefore, it is urgent to develop new functional materials with good biocompatibility and new technologies that specifically respond to tumors / tumor microenvironments to treat malignant tumors.
[0003] Chemodynamic therapy technology based on the specific in situ catalysis of Fenton reaction by nanoparticles responds to the acidic conditions of the tumor microenvironment and in situ catalyzes hydrogen peroxide in the tumor microenvironment to generate hydroxyl free radicals to kill tumor cells. It can effectively avoid the toxic side effects of radiotherapy and chemotherapy and is a new technology with great potential for cancer treatment. Due to the enhanced permeability and retention effect (EPR) in tumor tissues, only nanoparticles of a specific size can be enriched in tumor tissues through the gaps in tumor blood vessels. However, the weak acidity in the tumor microenvironment, the low concentration of hydrogen peroxide, and the particle size that does not match the gaps in tumor blood vessels make it difficult for Fe-based, Cu-based, and Mn-based nanodrugs commonly used in chemodynamic therapy to eradicate tumors.
[0004] In view of the application defects of the above-mentioned nanomedicines, the development of bimetallic nanomedicines has received extensive attention from researchers. For example, the Chinese invention patent with publication number CN118558325A discloses a bimetallic nanomedicine and its preparation method and application, the bimetallic nanomedicine includes a copper-cerium peroxide nanoparticle carrier and a drug carried thereon, the drug comprising doxorubicin, glucose oxidase and 1-methyl-tryptophan. The invention is based on the characteristics of copper-cerium bimetallic peroxide nanoparticles that exhibit excellent reactive oxygen species (ROS) and oxygen generation capabilities, and uses them as drug delivery carriers. Its nanostructure is used to enhance the anti-tumor effect of the drug, and its oxygen-producing properties are used to alleviate the hypoxic environment of the tumor, thereby improving the tumor microenvironment. In principle, the spherical or quasi-spherical nanoparticles decompose under the acidic microenvironment of the tumor, releasing H2O2, Cu 2+ , cerium ions and drug molecules. Among them, H2O2 and Cu 2+ The interaction produces a large amount of toxic ROS to enhance the therapeutic effect of CDT. Similarly, the Chinese invention patent with publication number CN118558325A provides a method for preparing a CeO2 / CuO2 composite nanomaterial with synergistic catalytic function, as well as the resulting products and applications. The scheme combines the inorganic nanomaterial CeO2 with CuO2, and then loads the chemotherapy drug doxorubicin (DOX) and further modifies hyaluronic acid (HA) to prepare a CeO2 / CuO2 composite nanomaterial with synergistic catalytic function. The invention uses the principle that CeO2 has good catalase activity to catalyze the decomposition of H2O2 in cells in the acidic environment of the tumor to produce a large amount of O2, thereby alleviating the tumor hypoxia and improving the chemotherapy effect of DOX. CeO2 / CuO2 composite nanomaterials can solve the problem of insufficient H2O2 content and improve the catalytic effect of Fenton-like reactions. CuO2 nanoparticles loaded by CeO2 nanospheres decompose and release H2O2 in the slightly acidic environment of tumor cells, which can increase the H2O2 content in tumor tissues, and then increase the concentration of ·OH through the Fenton reaction, thereby enhancing the effect of chemodynamic therapy (CDT).
[0005] The above bimetallic nanomedicines still have room for optimization in application. First of all, in terms of particle structure, the existing copper-cerium bimetallic nanoparticles are spherical or quasi-spherical. Since the surface of the sphere is completely symmetrical or approximately symmetrical, the distance from all points to the center is consistent. It has the greatest symmetry and the smallest surface area among all types of geometric shapes, and has the smallest ratio of surface area to volume. Therefore, the surface energy of the sphere tends to be minimized, which makes it difficult to perform various functionalizations on its surface through positive and negative electrical adsorption. At the same time, the size adjustment of nanomedicines in the prior art is complex and difficult to meet different usage requirements. In addition, in terms of the catalytic effect of the reaction, the prior art adopts Cu 2+ and Ce 3+ The formed peroxide nanoparticles may contain Ce 4+ With Cu 2+ The composite nanomaterials have limited catalytic activity towards H2O2 and reaction activity with glutathione (GSH), and the bimetallic synergistic catalytic ability and therapeutic effect need to be improved.
[0006] Therefore, designing and developing new nanomedicines that are activated by the weak acid environment of the tumor, self-supplied with hydrogen peroxide, and have controllable size for use in specific chemodynamic therapy technology, and providing combined treatment points with other tumor treatment technologies, is an urgent and significant task in the field of biomedical technology. Summary of the invention
[0007] In view of the above-mentioned defects of the prior art, in the first aspect of the present invention, a method for preparing hyaluronic acid functionalized copper-cerium bimetallic peroxide nano-octahedrons with simple process and controllable size is provided, comprising the following steps: (1) Dispersing a metal salt of cerium (IV) and a metal salt of copper (I) in an aqueous solution of polyvinylpyrrolidone (PVP) to form a bimetallic precursor solution; then adding sodium hydroxide and hydrogen peroxide to react to obtain copper-cerium bimetallic peroxide nanooctahedrons; The size of the product is controlled by adjusting the molecular weight of polyvinyl pyrrolidone, and the concentration of sodium hydroxide is adjusted to form an octahedral structure; (2) The obtained copper-cerium bimetallic peroxide nano-octahedron is coated with hyaluronic acid to obtain hyaluronic acid functionalized copper-cerium bimetallic peroxide nano-octahedron.
[0008] Preferably, in step (1), the metal salt of cerium (IV) includes one of cerium sulfate and cerium chloride; the metal salt of copper (I) includes one of cuprous sulfate, cuprous chloride and cuprous nitrate.
[0009] Preferably, in step (1), the molar ratio of the metal salt of cerium (IV), the metal salt of copper (I) and the water in the bimetallic precursor solution is 1-10:1-10:55.5.
[0010] Preferably, the step (1) adopts a controlled rate precipitation method, which specifically comprises the following steps: completely dissolving a metal salt of cerium (IV) and a metal salt of copper (I) in an aqueous solution of polyvinyl pyrrolidone to form a bimetallic precursor solution; then adding an aqueous sodium hydroxide solution and an aqueous hydrogen peroxide solution to the bimetallic precursor solution at a rate of 5-20 mL / h to react, and after the reaction is completed, recovering and purifying the product to obtain copper-cerium bimetallic peroxide nanooctahedra.
[0011] Further preferably, the volume ratio of the sodium hydroxide aqueous solution to the bimetallic precursor solution is 1:1-50; the volume ratio of the hydrogen peroxide aqueous solution to the bimetallic precursor solution is 1:1-25.
[0012] Further preferably, the concentration of the hydrogen peroxide solution is 0.39-9.79 mol / L.
[0013] The concentration of the sodium hydroxide aqueous solution needs to be controlled within an appropriate range. If the concentration of the sodium hydroxide aqueous solution is too low, the reaction will not be able to proceed completely and the octahedral structure will be difficult to form; if the concentration is too high, the cost will increase, and the number of washings will increase during the purification process, resulting in serious product loss and reduced yield.
[0014] Further preferably, in the process of adjusting the feeding concentration of sodium hydroxide to form the octahedral structure, the concentration of the sodium hydroxide aqueous solution is 1-20 mmol / L.
[0015] The smaller the molecular weight of PVP, the larger the size of the obtained copper-cerium bimetallic peroxide nano-octahedron; conversely, the larger the molecular weight of PVP, the smaller the size of the obtained copper-cerium bimetallic peroxide nano-octahedron. Therefore, the particle size can be easily adjusted by the molecular weight of PVP.
[0016] Preferably, in the step (1), in the aqueous solution of polyvinyl pyrrolidone, the molecular weight of polyvinyl pyrrolidone is 8000-58000; and the mass ratio of polyvinyl pyrrolidone to water is 1:5-20.
[0017] Preferably, in step (1), the reaction is carried out at room temperature and the reaction time is 1-12 h.
[0018] Preferably, the step (2) specifically comprises the following steps: dispersing the copper-cerium bimetallic peroxide nano-octahedron in water to obtain a dispersion; adding an aqueous solution of hyaluronic acid or sodium hyaluronate to the dispersion for reaction; after the reaction is completed, recovering and purifying the product to obtain hyaluronic acid functionalized copper-cerium bimetallic peroxide nano-octahedron.
[0019] Further preferably, the volume ratio of the dispersion to the aqueous solution of hyaluronic acid or sodium hyaluronate is 1:1-10.
[0020] Further preferably, in the dispersion, the mass ratio of copper-cerium bimetallic peroxide nanooctahedron to water is 1:500-1000; in the aqueous solution of hyaluronic acid or sodium hyaluronate, the mass ratio of hyaluronic acid or sodium hyaluronate to water is 1:500-1000.
[0021] Further preferably, the reaction is carried out at room temperature and the reaction time is 4-24 h.
[0022] In the second aspect of the present invention, a hyaluronic acid-functionalized copper-cerium bimetallic peroxide nanooctahedron with adjustable size, strong ability to actively target tumor tissue, high stability, good bimetallic synergistic catalytic ability and therapeutic effect is provided, which is prepared by the preparation method of the first aspect of the present invention.
[0023] In the third aspect of the present invention, there is provided an application of the hyaluronic acid functionalized copper-cerium bimetallic peroxide nano-octahedron according to the second aspect of the present invention, specifically, an application as an anti-tumor drug in tumor treatment.
[0024] Based on the above technical solutions, the design concept and principle of the present invention are as follows: The process of this method is simple and convenient. The target octahedral structure is obtained by adjusting the feeding concentration of sodium hydroxide, and the molecular weight of PVP is adjusted to achieve the purpose of size control. The required size and morphology can be selected according to the specific application. The prepared size-controlled hyaluronic acid functionalized copper-cerium bimetallic peroxide is more stable and more convenient to store than other metal peroxides due to the protective effect of hyaluronic acid on its surface. In addition, compared with spheres or spheroids, octahedral nanoparticles have some unique advantages in positive and negative electrical adsorption. First, the octahedral structure provides more surface active sites, which means that they can provide more adsorption sites, thereby improving the adsorption efficiency. Secondly, the geometric shape of octahedral nanoparticles leads to higher surface energy, which helps to enhance the interaction force with the adsorbed molecules. In the process of targeting tumors, hyaluronic acid functionalized copper-cerium bimetallic peroxide nanooctahedrons take advantage of the controllable size and passively target tumor tissues using the EPR effect. This nano-octahedron with positive charge on the surface can be functionalized in various ways through positive and negative charge adsorption, and can be adsorbed with negatively charged functional polymers such as hyaluronic acid to obtain functionalized nano-octahedron with negative charge on the surface. By functionalizing with hyaluronic acid, the ability of the active targeting of tumor tissue is improved.
[0025] According to the Nernst equation, under acidic conditions, E φ (Ce 4+ / Cu + ) = +1.567, and E φ (Cu 2+ / Ce 3+ ) =-1.567. This indicates that monovalent copper can reduce tetravalent cerium to trivalent cerium in a weakly acidic environment, while trivalent cerium cannot reduce divalent copper to monovalent copper. Therefore, when the elemental valence state composition of the copper-cerium bimetallic peroxide nanooctahedron is a ratio of monovalent copper element and tetravalent cerium / trivalent cerium, the bimetallic synergistic catalytic ability and therapeutic effect of the copper-cerium bimetallic peroxide nanooctahedron can be greatly improved. During tumor treatment, a series of cascade reactions are initiated by responding to the relatively high pH value in the tumor microenvironment, including: a large amount of tetravalent cerium ions, monovalent copper ions and hydrogen peroxide are released through weak acid response; the released tetravalent cerium ions are reduced to trivalent cerium ions with Fenton activity by monovalent copper ions and glutathione in the tumor microenvironment; trivalent cerium ions and monovalent copper ions further undergo a Fenton-like reaction to convert hydrogen peroxide into highly cytotoxic hydroxyl radicals, thereby achieving tumor-specific chemodynamic therapy.
[0026] In the process of tumor treatment, this bimetallic peroxide nano-octahedron with bimetallic synergy and cascade function can produce a variety of reactive oxygen species in tumor cells and tumor microenvironment through the above-mentioned cascade reaction, thereby enhancing the oxidative stress of tumor cells, releasing a large number of tumor antigens and damage-related molecular patterns, promoting the maturation of dendritic cells, inducing the polarization of tumor-associated macrophages to M1 type, activating effector T cells, and enhancing anti-tumor immune response. This realizes a complementary combined treatment method with immunotherapy mediated by anti-programmed death protein-1 antibody (αPD-1) and anti-programmed death receptor ligand-1 (αPD-L1), which can effectively solve the problem of poor therapeutic effect faced by single treatment methods. In the process of tumor treatment, combined with immunotherapy mediated by anti-programmed death protein-1 antibody (αPD-1), it can effectively inhibit the growth of primary tumors, prevent the occurrence of metastatic tumors, and significantly improve the efficacy of chemokinetic-immunotherapy.
[0027] Compared with the prior art, the present invention has the following advantages and beneficial effects: The invention provides a method for preparing hyaluronic acid functionalized copper-cerium bimetallic peroxide nano-octahedron, which has the advantages of simple process, controllable size and wide source of raw materials.
[0028] The present invention provides a hyaluronic acid functionalized copper-cerium bimetallic peroxide nano-octahedron, the size of the particle is adjustable, and the particles have the characteristics of strong ability to actively target tumor tissues, high stability, bimetallic synergistic catalytic ability and good therapeutic effect.
[0029] The present invention provides an application of hyaluronic acid functionalized copper-cerium bimetallic peroxide nano-octahedron, which has broad application prospects in tumor treatment as an anti-tumor drug. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 A flow chart of the preparation method of hyaluronic acid functionalized copper-cerium bimetallic peroxide nanooctahedron; Figure 2 The transmission electron microscope (TEM) images of copper-cerium bimetallic peroxide nano-octahedrons obtained at different sodium hydroxide feed concentrations are shown in FIG. Figure 2 A is the TEM image of copper-cerium bimetallic peroxide nanooctahedron obtained with a sodium hydroxide feed concentration of 1 mM. Figure 2 B is the TEM image of the copper-cerium bimetallic peroxide nanooctahedron obtained with a feed concentration of 5 mM sodium hydroxide. Figure 2 C is the TEM image of copper-cerium bimetallic peroxide nanooctahedron obtained with a feed concentration of 10 mM sodium hydroxide. Figure 2D is the TEM image of copper-cerium bimetallic peroxide nanooctahedron obtained by 20 mM sodium hydroxide feed concentration; Figure 3 TEM images of copper-cerium bimetallic peroxide nano-octahedra of different sizes obtained by feeding PVP with different molecular weights; Figure 3 A is the TEM image of the copper-cerium bimetallic peroxide nano-octahedron obtained by feeding 10000 MW molecular weight PVP. Figure 3 B is the TEM image of the copper-cerium bimetallic peroxide nano-octahedron obtained by feeding 24000 MW molecular weight PVP. Figure 3 C is the TEM image of copper-cerium bimetallic peroxide nanooctahedron obtained by feeding 48000 MW molecular weight PVP; Figure 4 Characterization of hyaluronic acid functionalized copper-cerium bimetallic peroxide nanooctahedra; wherein, Figure 4 A and 4B are TEM images of copper-cerium bimetallic peroxide nanooctahedra (CBPNs) and hyaluronic acid-functionalized copper-cerium bimetallic peroxide nanooctahedra (CBPNs@HA). Figure 4 C is a scanning transmission electron microscopy (STEM) image of hyaluronic acid functionalized copper-cerium bimetallic peroxide nanooctahedron. Figure 4 D is the element distribution diagram, Figure 4 E is the particle size test result, Figure 4 F is the X-ray photoelectron spectroscopy (XPS) test result of Ce3d orbital, Figure 4 G is the XPS test result of Cu2p orbital, Figure 4 H is the XPS test result of O1s orbital, Figure 4 I is the test result of producing H2O2 under different pH conditions, Figure 4 J is the potential test result; Figure 5 The cytotoxicity of CBPNs@HA and its ability to disrupt the intracellular redox balance; Figure 5 A is the toxicity results of different materials on B16 tumor cells. Figure 5 B is the toxicity results of different materials on CT26 tumor cells. Figure 5 C is the toxicity results of different materials on 4T1 tumor cells; Figure 6 is the in vivo antitumor effect of CBPNs@HA; Figure 5 A is the change in tumor size. Figure 5 B is the survival curve of tumor mice; Figure 5C is the weight change result; Figure 7 To construct CBPNs@HA and its anti-tumor mechanism in combination with αPD-1. DETAILED DESCRIPTION
[0031] The present invention will be specifically described below in conjunction with specific embodiments and examples, and the advantages and various effects of the present invention will be more clearly presented. It should be understood by those skilled in the art that these specific embodiments and examples are used to illustrate the present invention, but not to limit the present invention. Throughout the specification, unless otherwise specifically stated, the terms used herein should be understood as meanings commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. If there is a contradiction, this specification takes precedence. Unless otherwise specifically stated, various raw materials, reagents, instruments and equipment used in the present invention, etc., can be purchased from the market or can be obtained by existing methods.
[0032] The embodiment of the present invention provides a hyaluronic acid functionalized copper-cerium bimetallic peroxide nano-octahedron, such as Figure 7 As shown, the overall idea is as follows: According to another typical embodiment of the present invention, a method for preparing hyaluronic acid functionalized copper-cerium bimetallic peroxide nanooctahedron is provided, the method comprising: (1) Dispersing cerium (IV) metal salt and copper (I) metal salt in an aqueous solution of PVP, adding sodium hydroxide and hydrogen peroxide to obtain copper-cerium bimetallic peroxide nanooctahedron; As an optional implementation, the copper-cerium bimetallic peroxide nano-octahedron is synthesized by a controlled rate precipitation method, specifically comprising: The metal salt of cerium (IV) and the metal salt of copper (I) are completely dissolved in the aqueous solution of PVP to prepare a bimetallic precursor solution, and then a sodium hydroxide aqueous solution and a hydrogen peroxide solution are added to the bimetallic precursor solution through a pipe by a syringe pump at a rate of 20 mL / h for reaction, and the reaction solution is taken out and centrifuged and washed (8000-12000 rpm, 8-15 min) to obtain copper-cerium bimetallic peroxide nano-octahedron; Wherein, in the bimetallic precursor solution, the molar ratio of the metal salt of cerium (IV) to the metal salt of copper (I) is 1:1; The bimetallic precursor solution may be a cerium sulfate / cuprous sulfate aqueous solution, a cerium sulfate / cuprous chloride aqueous solution, a cerium sulfate / cuprous nitrate aqueous solution, a cerium chloride / cuprous chloride aqueous solution, a cerium chloride / cuprous nitrate aqueous solution or a cerium nitrate / cupric nitrate aqueous solution; The volume ratio of the sodium hydroxide aqueous solution to the bimetallic precursor solution is 1:1; the volume ratio of the hydrogen peroxide aqueous solution to the bimetallic precursor solution is 1:25; the mass volume ratio of PVP to water in the PVP aqueous solution is 1 g:4 mL; The feeding concentration of sodium hydroxide is adjusted to obtain copper-cerium bimetallic peroxide nano-octahedron; By changing the concentration of sodium hydroxide, the completeness of the reaction was changed, and copper-cerium bimetallic peroxide nano-octahedra with regular and uniform morphology were obtained. This step specifically includes: The concentration of the sodium hydroxide aqueous solution is adjusted, and then the remaining steps are performed to obtain copper-cerium bimetallic peroxide nano-octahedrons with gradually complete morphology; The feeding concentration of the sodium hydroxide aqueous solution is 1-20 mM; The molecular weight of PVP in the PVP aqueous solution is adjusted to obtain size-controlled copper-cerium bimetallic peroxide nano-octahedrons; PVP with different molecular weights is dissolved in water to obtain PVP aqueous solutions with different molecular weights, and then the subsequent steps are performed; This step specifically includes: The molecular weight of PVP in the PVP aqueous solution is adjusted to obtain PVP aqueous solutions with different molecular weights, and then the remaining steps are performed to obtain size-controllable copper-cerium bimetallic peroxide nano-octahedrons; Among them, the molecular weight of PVP in the PVP aqueous solution with different molecular weights is 10000-48000 Mw; (2) wrapping hyaluronic acid on the obtained copper-cerium bimetallic peroxide nano-octahedron to obtain hyaluronic acid-functionalized copper-cerium bimetallic peroxide nano-octahedron; This step specifically includes: Ultrasonic dispersion of copper-cerium bimetallic peroxide nano-octahedra in deionized water to obtain a dispersion; subsequently, a hyaluronic acid aqueous solution is added to the dispersion, centrifuged and washed after sufficient reaction to obtain size-controllable hyaluronic acid-functionalized copper-cerium bimetallic peroxide nano-octahedra; Wherein, the mass volume ratio of copper-cerium bimetallic peroxide nanooctahedron to deionized water in the dispersion is 1-10 mg:10 mL; The mass volume ratio of hyaluronic acid to deionized water in the hyaluronic acid aqueous solution is 1-10 mg:10 mL; The volume ratio of the dispersion to the hyaluronic acid aqueous solution was 1:1.
[0033] According to another typical embodiment of the present invention, provided is a size-controllable hyaluronic acid-functionalized copper-cerium bimetallic peroxide nano-octahedron prepared by the method.
[0034] The hyaluronic acid functionalized copper-cerium bimetallic peroxide nano-octahedron of the present application will be described in detail below in combination with the examples and experimental data.
[0035] Example 1 In this example, the preparation method of hyaluronic acid functionalized copper-cerium bimetallic peroxide nanooctahedron was used to prepare copper-cerium bimetallic peroxide nanooctahedron for studying its performance, and the steps were as follows: A bimetallic precursor solution was prepared by dissolving 1 mM cerium sulfate and 1 mM cuprous sulfate in deionized water containing 5 g PVP to obtain a bimetallic precursor solution and a 1 mM sodium hydroxide solution. The sodium hydroxide solution was then added to the reactor containing the bimetallic precursor solution by a syringe pump through an independent pipe at a rate of 20 mL / h, and the mixture was stirred at room temperature for 1 h. Subsequently, 1 mL of a 30 wt.% H2O2 aqueous solution was added to the reactor by a syringe pump through an independent pipe at a rate of 20 mL / h, and the mixture was reacted at room temperature for 1 h. After multiple centrifugation (10,000 rpm, 10 min) and washing, copper-cerium bimetallic peroxide nanooctahedra were obtained.
[0036] Example 2 In this example, the preparation method of hyaluronic acid functionalized copper-cerium bimetallic peroxide nanooctahedron was used to prepare copper-cerium bimetallic peroxide nanooctahedron for studying its performance, and the steps were as follows: A bimetallic precursor solution was prepared by dissolving 1 mM cerium sulfate and 1 mM cuprous sulfate in deionized water containing 5 g PVP to obtain a bimetallic precursor solution and a 5 mM sodium hydroxide solution. The sodium hydroxide solution was then added to the reactor containing the bimetallic precursor solution by a syringe pump through an independent pipe at 20 mL / h, and reacted for 1 h under stirring at room temperature. Subsequently, 1 mL of a 30 wt.% H2O2 aqueous solution was added to the reactor by a syringe pump through an independent pipe at 20 mL / h, and reacted at room temperature for 1 h. After multiple centrifugation (10,000 rpm, 10 min) and washing, copper-cerium bimetallic peroxide nanooctahedrons were obtained.
[0037] Example 3 In this example, the preparation method of hyaluronic acid functionalized copper-cerium bimetallic peroxide nanooctahedron was used to prepare copper-cerium bimetallic peroxide nanooctahedron for studying its performance, and the steps were as follows: A bimetallic precursor solution was prepared by dissolving 1 mM cerium sulfate and 1 mM cuprous sulfate in deionized water containing 5 g PVP to obtain a bimetallic precursor solution and a 10 mM sodium hydroxide solution. The sodium hydroxide solution was then added to the reactor containing the bimetallic precursor solution by a syringe pump through an independent pipe at 20 mL / h, and reacted for 1 h under stirring at room temperature. Subsequently, 1 mL of a 30 wt.% H2O2 aqueous solution was added to the reactor by a syringe pump through an independent pipe at 20 mL / h, and reacted at room temperature for 1 h. After multiple centrifugation (10,000 rpm, 10 min) and washing, copper-cerium bimetallic peroxide nanooctahedra were obtained.
[0038] Example 4 In this example, the preparation method of hyaluronic acid functionalized copper-cerium bimetallic peroxide nanooctahedron was used to prepare copper-cerium bimetallic peroxide nanooctahedron for studying its performance, and the steps were as follows: A bimetallic precursor solution was prepared by dissolving 1 mM cerium sulfate and 1 mM cuprous sulfate in deionized water containing 5 g PVP to obtain a bimetallic precursor solution and a 20 mM sodium hydroxide solution. The sodium hydroxide solution was then added to the reactor containing the bimetallic precursor solution by a syringe pump through an independent pipe at a rate of 20 mL / h, and the mixture was stirred at room temperature for 1 h. Subsequently, 1 mL of a 30 wt.% H2O2 aqueous solution was added to the reactor by a syringe pump through an independent pipe at a rate of 20 mL / h, and the mixture was reacted at room temperature for 1 h. After multiple centrifugation (10,000 rpm, 10 min) and washing, copper-cerium bimetallic peroxide nanooctahedra were obtained.
[0039] In this example, PVP was set to 10000 Mw, 24000 Mw, and 48000 Mw to prepare the corresponding copper-cerium bimetallic peroxide nano-octahedrons for studying the structural characteristics at different molecular weights.
[0040] Example 5 In this embodiment, the surface of copper-cerium bimetallic peroxide nano-octahedron is coated with sodium hyaluronate to complete functionalization, and hyaluronic acid functionalized copper-cerium bimetallic peroxide nano-octahedron is obtained, which is used to study its performance, such as Figure 1 As shown, the steps are as follows: (1) Prepare a bimetallic precursor solution, 1 mM cerium sulfate and 1 mM cuprous sulfate dissolved in deionized water containing 5 g PVP to prepare a bimetallic precursor solution and a 20 mM sodium hydroxide solution, then add the sodium hydroxide solution to the reactor containing the bimetallic precursor solution through an injection pump at 20 mL / h through an independent pipeline, and react for 1 h under stirring at room temperature; then add 1 mL of 30 wt.% H2O2 aqueous solution to the reactor through an injection pump at 20 mL / h through an independent pipeline, react for 1 h at room temperature, and then centrifuge (10000 rpm, 10 min) and wash several times to obtain copper-cerium bimetallic peroxide nanooctahedra (denoted as CBPNs); (2) Disperse 10 mg of CBPNs in 20 mL of deionized water and ultrasonicate for 5 min to uniformly disperse them to obtain a dispersion. Disperse 5 mg of hyaluronic acid in 20 mL of deionized water to prepare a hyaluronic acid aqueous solution. Add the above dispersion into the hyaluronic acid aqueous solution through an independent pipe by a syringe pump at a rate of 20 mL / h. Stir and react at room temperature for 4 h. After sufficient reaction, centrifuge and wash to obtain hyaluronic acid-functionalized copper-cerium bimetallic peroxide nanooctahedra (denoted as CBPNs@HA).
[0041] Example 6 In this embodiment, the surface of copper-cerium bimetallic peroxide nano-octahedron is coated with sodium hyaluronate to complete functionalization, and hyaluronic acid functionalized copper-cerium bimetallic peroxide nano-octahedron is obtained, which is used to study its performance, such as Figure 1 As shown, the steps are as follows: (1) Prepare a bimetallic precursor solution, 1 mM cerium sulfate and 1 mM cuprous sulfate are dissolved in deionized water containing 5 g PVP to prepare a bimetallic precursor solution and a 20 mM sodium hydroxide solution, then add the sodium hydroxide solution to the reactor containing the bimetallic precursor solution through an injection pump at 20 mL / h through an independent pipeline, and react for 1 h under stirring at room temperature; then add 1 mL of 0.39 mol / L H2O2 aqueous solution to the reactor through an injection pump through an independent pipeline at 20 mL / h, react for 1 h at room temperature, and then centrifuge (10000 rpm, 10 min) and wash several times to obtain copper-cerium bimetallic peroxide nanooctahedron; (2) Disperse 10 mg of copper-cerium bimetallic peroxide nano-octahedron in 20 mL of deionized water and ultrasonicate for 5 min to uniformly disperse it to obtain a dispersion; disperse 20 mg of hyaluronic acid in 20 mL of deionized water to prepare a hyaluronic acid aqueous solution; add the above dispersion into the hyaluronic acid aqueous solution through an independent pipe by a syringe pump at a rate of 20 mL / h, stir and react at room temperature for 24 h, centrifuge and wash after sufficient reaction to obtain hyaluronic acid-functionalized copper-cerium bimetallic peroxide nano-octahedron.
[0042] Example 7 (1) Prepare a bimetallic precursor solution, 1 mM cerium sulfate and 10 mM cuprous sulfate dissolved in deionized water containing 5 g PVP to prepare a bimetallic precursor solution and a 20 mM sodium hydroxide solution, then add the sodium hydroxide solution to the reactor containing the bimetallic precursor solution through an injection pump at 5 mL / h through an independent pipeline, and react for 1 h under stirring at room temperature; then add 1 mL of 9.79 mol / L H2O2 aqueous solution to the reactor through an injection pump at 5 mL / h through an independent pipeline, react for 1 h at room temperature, and then centrifuge (10000 rpm, 10 min) and wash several times to obtain copper-cerium bimetallic peroxide nanooctahedrons; (2) Disperse 10 mg of copper-cerium bimetallic peroxide nanooctahedra in 10 mL of deionized water and ultrasonicate for 5 min to uniformly disperse them to obtain a dispersion; disperse 20 mg of hyaluronic acid or sodium hyaluronate in 10 mL of deionized water to prepare a hyaluronic acid or sodium hyaluronate aqueous solution; add the above dispersion into the hyaluronic acid aqueous solution through an independent pipe by a syringe pump at a rate of 5 mL / h, stir and react at room temperature for 4 h, centrifuge and wash after sufficient reaction to obtain hyaluronic acid-functionalized copper-cerium bimetallic peroxide nanooctahedra.
[0043] Example 8 (1) Prepare a bimetallic precursor solution, 1 mM cerium sulfate and 5 mM cuprous sulfate dissolved in deionized water containing 5 g PVP to prepare a bimetallic precursor solution and a 20 mM sodium hydroxide solution, then add the sodium hydroxide solution to the reactor containing the bimetallic precursor solution through an injection pump at a rate of 10 mL / h through an independent pipeline, and react at room temperature for 1 h; then add 1 mL of 4.7 mol / L H2O2 aqueous solution to the reactor through an independent pipeline through a injection pump at a rate of 10 mL / h, react at room temperature for 1 h, and then centrifuge (10000 rpm, 10 min) and wash several times to obtain copper-cerium bimetallic peroxide nanooctahedrons; (2) Disperse 10 mg of copper-cerium bimetallic peroxide nanooctahedra in 15 mL of deionized water and ultrasonicate for 5 min to uniformly disperse them to obtain a dispersion; disperse 5 mg of hyaluronic acid or sodium hyaluronate in 15 mL of deionized water to prepare a hyaluronic acid or sodium hyaluronate aqueous solution; add the above dispersion into the hyaluronic acid aqueous solution through an independent pipe by a syringe pump at a rate of 10 mL / h, stir and react at room temperature for 14 h, centrifuge and wash after sufficient reaction to obtain hyaluronic acid-functionalized copper-cerium bimetallic peroxide nanooctahedra.
[0044] Test Example 1 Structural characterization of copper-cerium bimetallic peroxide nanooctahedra: This test example uses a transmission electron microscope to characterize the morphology and size of the copper-cerium bimetallic peroxides of different morphologies in Examples 1-4. Figure 2 As shown, under different sodium hydroxide feed concentrations, copper-cerium bimetallic peroxides exhibit different morphologies; Figure 2 As shown in A, at a feed concentration of 1 mM sodium hydroxide, the copper-cerium bimetallic peroxide exhibits an irregular granular structure; Figure 2 As shown in B, at a feed concentration of 5 mM sodium hydroxide, a small amount of octahedral structure appeared in the copper-cerium bimetallic peroxide; Figure 2 As shown in C, at a feed concentration of 10 mM sodium hydroxide, there are a large number of octahedral structures in the copper-cerium bimetallic peroxide, with only a small number of broken particles; Figure 2 As shown in Figure D, at a sodium hydroxide feed concentration of 20 mM, the copper-cerium bimetallic peroxide exhibits a nano-octahedral shape with regular structure and uniform size.
[0045] Test Example 2 Structural characterization of size-controlled Cu-Ce bimetallic peroxide nanooctahedra: This test example uses transmission electron microscopy to characterize the morphology and size of the copper-cerium bimetallic peroxide nanooctahedra prepared with different PVP molecular weights in Example 4. Figure 3 As shown, when using different molecular weights of PVP, the copper-cerium bimetallic peroxide nanooctahedra exhibit different sizes; Figure 3 As shown in A, when using 10000 Mw of PVP, the size of the copper-cerium bimetallic peroxide nanooctahedron is about 180 nm; Figure 3 As shown in B, when using 24000 Mw of PVP, the size of the copper-cerium bimetallic peroxide nanooctahedron is about 100 nm; Figure 3 As shown in C, when using 48000 MW of PVP, the size of the copper-cerium bimetallic peroxide nanooctahedron is about 50 nm.
[0046] Test Example 3 Structure and performance characterization of hyaluronic acid functionalized copper-cerium bimetallic peroxide nanooctahedra: The morphology and size of CBPNs@HA were characterized by transmission electron microscopy, scanning transmission electron microscopy and dynamic scattering. Figure 4 As shown in Figures 4A, 4B, and 4C, copper-cerium bimetallic peroxide and hyaluronic acid-functionalized copper-cerium bimetallic peroxide also present uniform nano-octahedral shapes; Figure 4 As shown in D, in the hyaluronic acid functionalized copper-cerium bimetallic peroxide nano-octahedron, the Cu, Ce, O, and N elements are evenly distributed on the surface of each nano-octahedron; Figure 4 As shown in E, the particle sizes of the obtained copper-cerium bimetallic peroxide nanooctahedron and hyaluronic acid functionalized copper-cerium bimetallic peroxide nanooctahedron are ~180 nm and ~190 nm, respectively.
[0047] The physical and chemical properties of the prepared hyaluronic acid functionalized copper-cerium bimetallic peroxide nanooctahedra were measured using an X-ray photoelectron spectrometer and an ultraviolet-visible spectrometer to determine whether the surface modification was successful, whether the properties of the material were affected, and the composition of the elements in the material; Figure 4 As shown in F and 4G, the valence distribution of Ce element in hyaluronic acid functionalized copper-cerium bimetallic peroxide nanooctahedron is Ce 4+ :Ce 3+ = 61.68%:31.21%, the valence state of Cu element is Cu + ;like Figure 4 As shown in H, there are obvious peroxide bonds in the hyaluronic acid-functionalized copper-cerium bimetallic peroxide nanooctahedra, indicating the presence of peroxide groups in the material; Figure 4 As shown in I, the ability of copper-cerium bimetallic peroxide nanooctahedron and hyaluronic acid functionalized copper-cerium bimetallic peroxide nanooctahedron to produce H2O2 under acidic conditions is similar, proving that the function of copper-cerium bimetallic peroxide nanooctahedron will not be affected during the functionalization process; Figure 4 As shown in Figure J, the surface of hyaluronic acid functionalized copper-cerium bimetallic peroxide nanooctahedron is negatively charged, while the surface of copper-cerium bimetallic peroxide nanooctahedron is positively charged, which proves the successful preparation of hyaluronic acid functionalized copper-cerium bimetallic peroxide nanooctahedron.
[0048] Application Example 1 In vitro experiments: In vitro co-culture experiments were carried out with B16, CT26 and 4T1 tumor cells and the prepared CBPNs@HA to systematically study the in vitro anti-tumor properties and mechanisms of the material.
[0049] Including: Tumor cytotoxicity. First, B16 / CT26 / 4T1 cells were seeded in 96-well plates (1×10 5 cells / well) were cultured in complete 1640 RPMI medium (containing 10% fetal bovine serum and 1% penicillin and streptomycin) for 24 h. To verify that CBPNs@HA responds to the weakly acidic pH of the tumor microenvironment, hyaluronic acid-functionalized copper-cerium bimetallic peroxide nanooctahedra were co-cultured with B16 / CT26 / 4T1 tumor cells in medium with pH 6.8 and 7.2 for 24 h, and then 10% CCK8 solution was added and incubated for 1.5 h. The absorbance of each well at a wavelength of 450 nm was measured using an ELISA reader. Figure 5 As shown in Figures AC, in the culture medium with a pH of 6.8, a large number of tumor cells were killed by CBPNs and CBPNs@HA materials, while when the pH of the culture medium was 7.2, only a portion of the tumor cells were killed by CBPNs and CBPNs@HA materials. At the same time, CBPNs@HA was more toxic to tumor cells, indicating that CBPNs@HA can further enhance the uptake of tumor cells, selectively respond to the pH of the culture environment, and enhance its toxicity to tumor cells.
[0050] Application Example 2 In vivo antitumor properties of hyaluronic acid-functionalized copper-cerium bimetallic peroxide nanooctahedra and enhanced αPD-1-mediated immunotherapy: BALB / c mice aged 6-8 weeks were used as model animals. A 4T1 tumor-bearing mouse model was established by subcutaneous injection of 4T1 tumor cells. The effect of CBPNs@HA on tumor treatment and the therapeutic effect of combined treatment with αPD-1 after tail vein injection were systematically studied. 3 At the same time, the tumor-bearing mice were randomly divided into six groups, and the corresponding drug administration methods were injected into the mice through the tail vein on days 8 and 9, days 11 and 12, days 14 and 15, and days 17 and 18. Every other day, the weight changes and tumor size changes of the mice were recorded and the tumor volume was calculated (Still formula: V=W2×L / 2, W is the short diameter length of the tumor, L is the long diameter length of the tumor).
[0051] like Figure 6As shown in the figure, compared with other control materials (the control materials include PBS, αPD-1 and CBPNs), after treatment with hyaluronic acid functionalized copper-cerium bimetallic peroxide nanooctahedron CBPNs@HA, the tumor growth of tumor-bearing mice was significantly inhibited, and the tumor volume was significantly smaller than that of other materials, indicating that CBPNs@HA has a good inhibitory effect on tumor growth. After synergistic treatment with αPD-1, the tumor growth of tumor-bearing mice was further inhibited, and the tumor volume was more significantly reduced compared with the CBPNs@HA group, and there was no recurrence after the end of treatment.
[0052] Among them, the therapeutic effect of αPD-1 alone was not good; at the same time, CBPNs were unfunctionalized copper-cerium bimetallic peroxide nanooctahedra, and the therapeutic effect was not good, and the tumor recurred after the treatment; CBPNs@HA functionalized with hyaluronic acid showed good therapeutic effects on tumors in tumor-bearing mice during the treatment period, but the tumor recurred during the observation period after the treatment; the treatment group combined with αPD-1 and CBPNs@HA showed good tumor inhibition effects during and after the treatment, and no recurrence occurred. This shows that CBPNs@HA can actively target the tumor area, and after combining with αPD-1, it can significantly enhance the body's anti-tumor immunity, enhancing αPD-1-mediated anti-tumor immunotherapy.
[0053] In summary, the size-controllable hyaluronic acid-functionalized copper-cerium bimetallic peroxide nanooctahedra prepared by the present invention utilizes the active tumor targeting ability provided by hyaluronic acid to improve the enrichment effect of nanooctahedra in tumors. After targeting the tumor site, the hyaluronic acid-functionalized copper-cerium bimetallic peroxide nanooctahedra can initiate a series of cascade reactions, effectively causing a Fenton-like reaction, thereby amplifying oxidative stress and effectively inducing immunogenic cell death in tumor cells, thereby enhancing the immunotherapy effect. In this cascade reaction, the nanooctahedra decompose at a relatively high pH in the tumor microenvironment to produce H2O2, Cu + and Ce 4+ , Ce 4+ Cu + and glutathione in tumors is reduced to Ce 3+ , Ce 3+ / Cu + It reacts with H2O2 in the tumor and self-supplied H2O2 in a Fenton-like reaction to produce highly cytotoxic ·OH, which causes immunogenic death by enhancing oxidative stress, thereby releasing a large number of tumor antigens and damage-related molecular patterns, thereby promoting the maturation of dendritic cells, inducing tumor-associated macrophages to polarize to the M1 type, activating effector T cells, and enhancing anti-tumor immune effects. Figure 7As shown, the design and development of this copper-cerium bimetallic peroxide nanooctahedron provides a new strategy for efficient chemodynamic therapy and a new idea for the combined treatment of chemodynamic-immunotherapy.
[0054] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution that can be obtained by a person skilled in the art through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection determined by the claims.
Claims
1. A method for preparing hyaluronic acid functionalized copper-cerium bimetallic peroxide nanooctahedrons, characterized in that: The steps include: (1) dispersing a metal salt of cerium (IV) and a metal salt of copper (I) in an aqueous solution of polyvinyl pyrrolidone to form a bimetallic precursor solution; then adding sodium hydroxide and hydrogen peroxide to react to obtain copper-cerium bimetallic peroxide nanooctahedrons; The size of the product is controlled by adjusting the molecular weight of polyvinyl pyrrolidone, and the concentration of sodium hydroxide is adjusted to form an octahedral structure; (2) The obtained copper-cerium bimetallic peroxide nano-octahedron is coated with hyaluronic acid to obtain hyaluronic acid functionalized copper-cerium bimetallic peroxide nano-octahedron.
2. The method for preparing hyaluronic acid functionalized copper-cerium bimetallic peroxide nanooctahedron according to claim 1, characterized in that: In the step (1), the metal salt of cerium (IV) includes one of cerium sulfate and cerium chloride; the metal salt of copper (I) includes one of cuprous sulfate, cuprous chloride and cuprous nitrate.
3. The method for preparing hyaluronic acid functionalized copper-cerium bimetallic peroxide nanooctahedron according to claim 1, characterized in that: In the step (1), the molar ratio of the metal salt of cerium (IV), the metal salt of copper (I) and the water in the bimetallic precursor solution is 1-10:1-10:55.
5.
4. The method for preparing hyaluronic acid functionalized copper-cerium bimetallic peroxide nanooctahedron according to claim 1, characterized in that: The step (1) adopts a controlled rate precipitation method, which specifically comprises the following steps: completely dissolving a metal salt of cerium (IV) and a metal salt of copper (I) in an aqueous solution of polyvinyl pyrrolidone to form a bimetallic precursor solution; then adding an aqueous sodium hydroxide solution and an aqueous hydrogen peroxide solution to the bimetallic precursor solution at a rate of 5-20 mL / h to react, and after the reaction is completed, recovering and purifying the product to obtain copper-cerium bimetallic peroxide nano-octahedrons.
5. The method for preparing hyaluronic acid functionalized copper-cerium bimetallic peroxide nanooctahedron according to claim 4, characterized in that: The volume ratio of the sodium hydroxide aqueous solution to the bimetallic precursor solution is 1:1-50; the volume ratio of the hydrogen peroxide aqueous solution to the bimetallic precursor solution is 1:1-25; the concentration of the hydrogen peroxide solution is 0.39-9.79 mol / L; in the process of adjusting the feeding concentration of sodium hydroxide to form an octahedral structure, the concentration of the sodium hydroxide aqueous solution is 1-20mmol / L.
6. The method for preparing hyaluronic acid functionalized copper-cerium bimetallic peroxide nanooctahedron according to claim 1, characterized in that: In the step (1), the molecular weight of polyvinyl pyrrolidone in the aqueous solution is 8000-58000; the mass ratio of polyvinyl pyrrolidone to water is 1:5-20; the reaction is carried out at room temperature and the reaction time is 1-12 h.
7. The method for preparing hyaluronic acid functionalized copper-cerium bimetallic peroxide nanooctahedron according to claim 1, characterized in that: The step (2) specifically comprises the following steps: dispersing the copper-cerium bimetallic peroxide nano-octahedron in water to obtain a dispersion; adding an aqueous solution of hyaluronic acid or sodium hyaluronate to the dispersion to react; and after the reaction is completed, recovering and purifying the product to obtain hyaluronic acid functionalized copper-cerium bimetallic peroxide nano-octahedron.
8. The method for preparing hyaluronic acid functionalized copper-cerium bimetallic peroxide nanooctahedron according to claim 7, characterized in that: The volume ratio of the dispersion liquid to the aqueous solution of hyaluronic acid or sodium hyaluronate is 1:1-10; in the dispersion liquid, the mass ratio of copper-cerium bimetallic peroxide nanooctahedron to water is 1:500-1000; in the aqueous solution of hyaluronic acid or sodium hyaluronate, the mass ratio of hyaluronic acid or sodium hyaluronate to water is 1:500-1000; the reaction is carried out at room temperature and the reaction time is 4-24 h.
9. A hyaluronic acid functionalized copper-cerium bimetallic peroxide nanooctahedron, characterized in that: The method is prepared according to any one of claims 1 to 8.
10. An application of the hyaluronic acid functionalized copper-cerium bimetallic peroxide nano-octahedron as claimed in claim 9, characterized in that: Application as an anti-tumor drug in tumor treatment.
Citation Information
Patent Citations
Nano cerium peroxide catalyst and method for catalyzing TMB color development by using same
CN111060501A
Cerium dioxide-based nanopowder, antibacterial film, and preparation method and application of cerium dioxide-based nanopowder
CN117105256A
Preparation method and application of bimetallic Ce-Cu-MOFs derivative catalyst
CN117483008A
Bimetal-based nano-drug as well as preparation method and application thereof
CN118453880A
Preparation method of CeO2 / CuO2 composite nanomaterial with synergistic catalysis function, obtained product and application
CN118558325A
